2021
DOI: 10.1038/s41366-021-01052-5
|View full text |Cite
|
Sign up to set email alerts
|

Weight-based stereotype threat in the workplace: consequences for employees with overweight or obesity

Abstract: Background/Objectives Employees with overweight or obesity are often stereotyped as lazy, unmotivated, and less competent than employees with normal weight. As a consequence, employees with overweight or obesity are susceptible to stereotype threat, or the concern about confirming, or being reduced to, a stereotype about their group. This survey study examined whether employees with overweight or obesity experience stereotype threat in the workplace, whether it is associated with their perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…According to Vanhove and Gordon (2014), overweight and obese employees experience greater amounts of negative work-related outcomes such as lower employment and income when compared to employees who are considered to be of a normal weight. Zacher and Von Hippel (2021) found that employees experience stereotype threat related to their weight and that weight-based stereotype threat is associated with employees experiencing lower self-perceived work ability. Currently, this is one of the only studies to explicitly examine the relationship between weight-based stereotype threats and overweight employees' self-perceived work outcomes.…”
Section: Background Work On Stereotype Threat Researchmentioning
confidence: 96%
“…According to Vanhove and Gordon (2014), overweight and obese employees experience greater amounts of negative work-related outcomes such as lower employment and income when compared to employees who are considered to be of a normal weight. Zacher and Von Hippel (2021) found that employees experience stereotype threat related to their weight and that weight-based stereotype threat is associated with employees experiencing lower self-perceived work ability. Currently, this is one of the only studies to explicitly examine the relationship between weight-based stereotype threats and overweight employees' self-perceived work outcomes.…”
Section: Background Work On Stereotype Threat Researchmentioning
confidence: 96%
“…Data for this study were collected as part of a larger data collection effort with five measurement waves, and three other studies based on the same dataset, but with completely different research question and completely different substantive variables, have been published (Weiss & Zacher, 2022;Zacher & Rudolph, 2022;Zacher & von Hippel, 2022). The five measurement waves consisted of one initial survey that asked questions regarding demographics (Bensemmane et al, 2018).…”
Section: Procedures and Participantsmentioning
confidence: 99%
“…Study has reported a correlation between job capacity limitations and several factors such as musculoskeletal discomfort, chronic illness, absenteeism, premature retirement, and overall mortality 3 . Overweight or obesity employees are often subject to negative stereotypes, such as being seen as lacking in motivation, laziness, and lower levels of competence compared to employees who have a normal weight 4 . Reduced WA may indicate cardiovascular diseases (CVDs), physical, mental, and social instability 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…obesity employees are often subject to negative stereotypes, such as being seen as lacking in motivation, laziness, and lower levels of competence compared to employees who have a normal weight. 4 Reduced WA may indicate cardiovascular diseases (CVDs), physical, mental, and social instability. 5,6 Physical, mental, and social instability can lead to negative weight, body mass index (BMI), waist circumference (WC), and waist-to-hip ratio, obesity, and related health hazards.…”
mentioning
confidence: 99%